Two Death Cases Due to Motor Vehicle Heating System (Webasto) – Cases Report - Bütün, Celal; Polater, Erdogan; Beyaztaş, Fatma Yücel (The Bulletin of Legal Medicine, 2019)
With the mechanism of motor vehicle heating systems operating with minimum fuel; the outside air is passed through the radiator and the desired temperature is provided inside the vehicle and air is blown by the electrophysiological to different parts of the vehicle. Thus, in cold weather, the desired temperature for the vehicle is provided and it is ensured that inside of the vehicle is not air-free. However, for efficient operation of the heating and ventilation system, which is used as a standard in motor vehicles, it is necessary to periodically check and maintain the system. In this study; by two deadly cases due to carbon monoxide poisoning arising from the failure of the motor vehicle heating system of parked truck the importance of being supervised these systems in a controlled manner is emphasized. Key Words: Motor vehicle heating system, Asphyxia, Carbon monoxide, Autopsy, Webasto.